School Environmental Education Activities to Enhance Plant Utilization for Students at SDN Kuin Cerucuk V, Banjarmasin City - Kaspul Kaspul; Nurul hidayati Utami (Pascasarjana Universitas Mataram, 2024)
Students' knowledge about plants is crucial. The school environment serves not only as a place containing various types of plants but also as a learning resource. Some plants available in the school environment have the potential for medicinal use as well as aesthetic purposes. The purpose of this activity is to enhance student's knowledge about the utilization of plants in the school environment through educational activities at SDN Kuin Cerucuk V, Banjarmasin. The activity was conducted at SDN Kuin Cerucuk V with 64 students from grades 4, 5, and 6, along with 7 teachers. Besides the importance of conducting education about medicinal plants, similar activities regarding the utilization of medicinal plants in the vicinity of SDN Kuin Cerucuk V, Banjarmasin, have not been conducted before. Based on the service results, it is known that the educational activity on the utilization of plants around the environment shows a positive response and enthusiasm. The educational activities were carried out through lectures in classrooms and using posters as a publication medium. The results of the education show that there was an increase in students' knowledge, with a pre-education average of 10.91 and a post-education average of 89.01. The improvement in knowledge can contribute to teaching and learning activities